ANALISIS KINERJA KEUANGAN DALAM MENINGKATKAN VOLUME PERDAGANGAN SAHAM PADA BANK SYARIAH INDONESIA PERIODE 2021-2023 - Nuriatullah; Annisa Waridh; Dede Arseyani Pratamasyari; Noor Riefma Hidayah (Jariyah: Jurnal Ilmu Akuntansi dan Keuangan Syariah, 2025)
This study aims to analyze the impact of financial performance on the trading volume of Bank Syariah Indonesia (BSI) shares on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The primary focus is to evaluate how financial performance indicators, such as Return on Equity (ROE), Market Value Added (MVA), Cash Ratio, and Debt to Equity (DER), influence the trading volume of BSI shares. The approach employed in this research is qualitative, utilizing a descriptive research design. Secondary data were used, derived from the annual financial reports of Bank Syariah Indonesia (BSI) and the official Indonesia Stock Exchange website, which provides stock price data. The research methodology involves analyzing BSI’s financial and trading data to identify the relationship between financial performance and trading volume. The analysis results indicate that the company’s financial performance improved with an increase in Return on Equity (ROE) from 2021 to 2023, particularly in the first quarter of 2023. A high Market Value Added (MVA) in 2023 signifies value creation exceeding capital costs, although it has declined since 2021. The declined in the Cash Ratio affected perceptions of financial security, and a high Debt to Equity Ratio (DER) raised concerns about risk. Share trading volume was volatile, increasing in the first quarter of 2023 alongside higher ROE and MVA, but declining in subsequent quarters due to concerns over DER and the Cash Ratio. These fluctuations reflect investor sensitivity to debt risk and the company’s financial health. The findings suggest that increases in ROE and MVA tend to boost trading volume, while a declining Cash Ratio and high DER may trigger investor concerns, impacting market liquidity.